Der Weltanschauungsroman 2. Ordnung Probleme literarischer Modellbildung bei Hermann Broch und Robert Musil - Schwarzwälder, Florens (Lettre, 2019)
Between the world wars, Robert Musil and Hermann Broch replied to an era of catastrophes, which they brought close to their bodies with their protagonists, who were entangled in ideological salvation hopes: a pathogenesis of the bourgeois world for the 1930s. The fact that after 1933 they took their contemporaries' longing for a "world view" more and more seriously has often irritated the newborn. However, her »2nd order world view novel«, which is being unfolded here for the first time, still testifies to the enormous historical project of engaging with the language of the time and tracking down its most fatal tendencies with literary empathy and critical distance.